Kuzmenko A.G. Variation-experimental method in contact mechanics of moving from a change and tensions. - Кузьменко, А.Г. (Problems of Tribology, 2014)
The variation-experimental method of decision of contact tasks about the plastic pressing of indentors is widespread on the decision of contact tasks about the nonlinear (plasticity or sliding) change of pinned indentor. A task is taken to one equalization of equilibrium which succeeds to be decided as a two-parameter function of tensions of friction. In more general case a task is taken to the quadratic functional, to containing as the known function of diagram of change of indentor. A list is resulted from ten basic problems of similar tasks about the change of indentora. The decision of tasks from the resulted list can be executed in the first approaching by equalization of equilibrium, and more exactly by the functional of process.